Yield gap analyses to inform policy on sustainable crop intensification pathways in Uganda - Walukano, W.; Pali, Pamela N.; Wairegi, L.W.I.; Nanfumba, D.; Arinaitwe, A.; Basalirwa, D.; Asiimwe, R.; Asten, Piet J.A. van (Tropentag, 2016)
Smallholder potato yields in Uganda are low (<4.7 tha-1) compared to 25 tha-1 attainable on-station yields, attributed to: poor quality seed, low soil fertility, pests and diseases, limited knowledge and weak policy environment. Potatoes however represent about half of the total monetary value of crop production in Uganda’s Southwestern highlands.Development and policy actors wish to intensify potato systems to sustain rural livelihoods and high population growing at 3.4% per annum. The agronomy study was undertaken to understand how genotype x environment x management interactions affect potato yields at plot, farm and community levels to generate evidence for stimulating policy action relevant to crop intensification. The objectives of the study were to; (1) analyze the magnitude of the yield gap by determining attainable and actual potato yields, (2) establish the resource utilization (land, seed quality and fertilizers) and management practices for potato production (3) develop policy recommendations to largest potato yield to support increase and improve potato production systems in Uganda. The study was conducted in 2014- 2015 in the highlands of Southwestern Uganda using a total of 283 households in rainfed potato farms surveyed for: production and crop management, access to services and technologies. Households were selected using stratified cluster sampling. Yield data obtained were compared to on-station yields to establish the yield gap. Results show a large yield gaps (60-80%) exist between average farmer and best on-station yield. The results suggest that seed is the major limiting constraint in potato cropping systems. Households using good quality seed potato obtained an average 11.1 tha-1 versus 6.4 tha-1 for those using poor quality seed. On-station yields reach 25 tha-1. It can be concluded that Uganda has the potential to more than double the yield if an enabling policy environment of increasing access to quality seed for potato is created. This can be through the National Seed Policy to guide production marketing, distribution and access to quality seed for smallholder potato farmers. Sustainable intensification would require easy access to key yield augmenting inputs used in a stepwise approach starting with quality seed and then other complementary inputs.